Portrait in jazz [compact disc] - Evans, Bill, 1929-1980; LaFaro, Scott; Motian, Paul (Keepnews collection., 2008)
This reissued album features bassist Scott LaFaro and drummer Paul Motian, and introduced a new kind of swing based on a flexible sense of time and interplay.